2023
DOI: 10.1021/acsfoodscitech.2c00354
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethylpachymaran-Coated Zein Nanoparticles for Oral Delivery of Curcumin: Formation, Characterization, Physicochemical Stability, and Controlled Release Properties

Abstract: The instability and poor solubility of curcumin limit its intake in the human body. In this work, curcuminencapsulated carboxymethylpachymaran/zein composite nanoparticles (ZMCNPs) were prepared by anti-solvent precipitation, and the morphology of composite nanoparticles was confirmed by transmission electron microscopy, and the interaction between carboxymethylpachymaran, zein, and curcumin was explored by Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetric analysis, and differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…This suggests that near-neutral charge conditions at pH = 7 favor optimal packing within the nanoparticles, allowing for an increased loading of bioactive compounds. These results emphasize the significance of pH in the formulation of zein nanoparticles for efficient bioactive delivery. , …”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…This suggests that near-neutral charge conditions at pH = 7 favor optimal packing within the nanoparticles, allowing for an increased loading of bioactive compounds. These results emphasize the significance of pH in the formulation of zein nanoparticles for efficient bioactive delivery. , …”
Section: Resultsmentioning
confidence: 52%
“…These results emphasize the significance of pH in the formulation of zein nanoparticles for efficient bioactive delivery. 10,31 3.3. Morphological Analysis.…”
Section: Effect Of Ph On Zein Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al designed carboxymethylpachymaran‐coated zein nanoparticles as a smart DDS for curcumin which could intelligently control the release curcumin and prevent the premature release of curcumin in the stomach. [ 62 ] The developed system, it may be argued, can distribute medications in a regulated way for a long period of time. [ 63 ] Increased release at pH 5 suggests that the DDS is suitable for anticancer applications.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this criticality, it has been observed that the use of a core shell as a natural polyelectrolyte, such as hyaluronic acid, pectin, carboxymethyl chitosan, carboxymethyl dextrin, soy polysaccharide, or rubber, stabilizes the nanoparticles; this allows for a good stability of pH and ionic strength, increasing the encapsulation efficiency compared to single ZNPs. Moreover, smaller nanoparticle size leads to a longer release time for the active ingredients [ 52 ].…”
Section: Zein: Structure Properties and Current Applicationsmentioning
confidence: 99%